Hospital-based health technology assessment (HTA) in Latin America and the Caribbean: a scoping review - Alex Itaborahy; Vania Cristina Canuto Santos; Flávia Cristina Ribeiro Salomon; Caroline Bregman; Iandy Mateus; Marisa Santos (Revista Panamericana de Salud Pública)
Objective. To provide an overview of hospital-based health technology assessment (HB-HTA) activities in Latin America and the Caribbean, including the technologies assessed, resources utilized, evaluation methods employed, and challenges encountered. Methods. A scoping review focused on HB-HTA using frameworks from the Joanna Briggs Institute was conducted across databases and gray literature. Results. Seventeen studies were identified, and another two documents were retrieved manually at a conference, totaling 19 files. Brazil emerged as a key player in HB-HTA activities in Latin America and the Caribbean, with public teaching hospitals leading the efforts. The primary focus of HB-HTA units was assessing medicines/pharmaceuticals and medical devices, using budget impact and cost-effectiveness/utility analyses as the main appraisal tools. The review also identified challenges such as limited human resources and financial support. Conclusions. The study highlights a growing interest in HB-HTA in Latin America and the Caribbean, driven primarily by public institutions. The findings underscore the need for tailored approaches to strengthen evidence-based decision-making in healthcare settings and address the challenges of the region’s limited resources and financial constraints.